2011
DOI: 10.1093/europace/eur199
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors and echocardiographic techniques related to the presence, size, and location of acoustic windows for leadless cardiac pacing

Abstract: Adequate AWs were present in nearly all patients. Despite smaller hearts, ischaemic cardiomyopathy patients had adequate AWs. A simple procedure performed as an adjunct to pre-implant echocardiography can screen patients and identify transmitter implant locations for an ultrasound-mediated leadless pacing system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The best acoustic window, which is known to vary with patient movement and respiration, is usually found in the 4th, 5th, and/or 6th intercostal space lateral of the left parasternal border. 20 The receiver/pulse generator is delivered retrogradely across the aortic valve to the desired endocardial pacing site of the left ventricle. Fixation to the endocardium is achieved with three self-expanding nitinol tines mounted at the distal end of the device.…”
Section: Implantation Of Leadless Pacemakersmentioning
confidence: 99%
“…The best acoustic window, which is known to vary with patient movement and respiration, is usually found in the 4th, 5th, and/or 6th intercostal space lateral of the left parasternal border. 20 The receiver/pulse generator is delivered retrogradely across the aortic valve to the desired endocardial pacing site of the left ventricle. Fixation to the endocardium is achieved with three self-expanding nitinol tines mounted at the distal end of the device.…”
Section: Implantation Of Leadless Pacemakersmentioning
confidence: 99%
“…The transmitter is always implanted first, and therefore once implantation has occurred, this may limit the potential endocardial sites available. 5 Prior studies have shown that an increased separation between the electrode and the transmitter results in failure of biventricular pacing. 2 Once the target location of the electrode is known, preprocedural calculation of the acoustic intensity at the target electrode site for each potential transmitter site allows the optimal transmitter site to be selected, which may result in reliable right ventricualr (RV) tracking, biventricular pacing, and improved outcomes.…”
Section: Introductionmentioning
confidence: 99%